The Landscape of mtDNA Modifications in Cancer: A Tale of Two Cities - Hertweck, Kate L.; Dasgupta, Santanu (Frontiers in Oncology, 2017)
Mitochondria from normal and cancerous cells represent a tale of two cities, wherein both execute similar processes but with different cellular and molecular effects. Given the number of reviews currently available which describe the functional implications of mitochondrial mutations in cancer, this article focuses on documenting current knowledge in the abundance and distribution of somatic mitochondrial mutations, followed by elucidation of processes which affect the fate of mutations in cancer cells. The conclusion includes an overview of translational implications for mtDNA mutations, as well as recommendations for future research uniting mitochondrial variants and tumorigenesis.